Combined immunotherapy with anti-PDL-1/PD-1 and anti-CD4 antibodies cures syngeneic disseminated neuroblastoma. Issue 1 (December 2017) - Rigo, Valentina; Emionite, Laura; Daga, Antonio; Astigiano, Simonetta; Corrias, Maria; Quintarelli, Concetta; Locatelli, Franco; Ferrini, Silvano; Croce, Michela
Abstract Anti-PD-1 or anti-PD-L1 blocking monoclonal antibodies (mAbs) have shown potent anti-tumor effects in adult cancer patients and clinical studies have recently been started in pediatric cancers, including high-risk/relapsing neuroblastoma (NB). Therefore, we studied the effects of anti-PD-1/PD-L1 mAbs in two syngeneic models of disseminated NB generated by the injection of either Neuro2a or NXS2 cells, which express PD-L1. In addition, we tested the combination of these agents with the immune-enhancing cytokine IL-21, the Ecto-NTPDase inhibitor POM-1, an anti-CD25 mAb targeting Treg cells, or an anti-CD4 mAb. We previously showed that CD4-transient depletion removes CD4+ CD25+ Treg cells and other CD4+ CD25− regulatory subsets. Here we show that mono-therapy with anti-PD-1/PD-L1 mAbs had no effect on systemic NB progressionin vivo, and also their combination with IL-21, POM-1 or anti-CD25 mAb was ineffective. The combined use of anti-PD-1 with an anti-CD4 mAb mediated a very potent, CD8-dependent, synergistic effect leading to significant elongation of tumor-free survival of mice, complete tumor regression and durable anti-NB immunity. Similar results were obtained by combining the anti-PD-L1 and anti-CD4 mAbs. These findings indicate that both PD-1/PD-L1 and CD4+ T cell-related immune-regulatory mechanisms must be simultaneously blocked to mediate therapeutic effects in these models.